Analysis of the distribution of equalizing grants for budgets of constituent entities of the Russian Federation - A. A. Bishenov; L. H. Ittieva (Путеводитель предпринимателя)
In the system of inter-budgetary relations in the Russian Federation, subsidies for equalizing the budget provision of regions take priority. The article analyzes their distribution, mainly for the subjects of the southern and North Caucasus Federal districts, as regions with the lowest budget security. The authors put forward proposals to improve the efficiency of the distribution of equalizing subsidies to the budgets of the Russian Federation’s constituent entities.